The Molecular Links of Re-Emerging Therapy: A Review of Evidence of Brahmi (Bacopa monniera) - Mathur, Deepali; Goyal, Kritika; Koul, Veena; Anand, Akshay (Frontiers in Pharmacology, 2016)
The convolution associated with memory is being resolved with advancement in neuroscience. According to the concurrent assumptions, synaptic plasticity forms one of the basis of memory formation, stabilization and strengthening. In Alzheimer's disease (AD), which is generally characterized by memory dysfunction, connections amongst the cells in the brain are attenuated or lost leading to degeneration, of neural networks. Numerous attempts have been made to find new therapies for memory dysfunction with increasing attention and investments being laid on herbal drugs. Many herbal plants and extracts have already documented beneficial results when tested for antiamnesic effects. Brahmi (Bacopa monniera) is one such common herbal drug, which is employed for a long time in the Indian and chinese medical system in order to treat several disorders. Previous research has shown that Brahmi exerts many pharmacological effects including memory boosting capacity in the treatment of Alzheimer’s disease and Schizophrenia, exhibiting antiparkinsonian, antistroke, and anticonvulsant potentials. The present review discusses the chemical constituents of Brahmi along with in vitro and in vivo studies based on the pharmacological effects exerted by it. The efficacy of Brahmi in treating various disorders has evoked sufficient research in recent years and time is ripe to launch multiple clinical trials.